Beyond the digital diaspora: YouTube methodologies, online networking, and the Hmong Music Festival - Ó Briain, Lonán (Equinox Publishing, 2015)
This article examines attempts by American Hmong to turn the thriving Hmong digital diaspora into a sustainable offline musical community. The Hmong, an ethnic group of five million people spread across five continents, have embraced YouTube as a primary source for Hmong music recordings. Online research on Hmong users with the aid of YouTube Analytics is informed by extensive periods of fieldwork with the Hmong in Vietnam and shorter encounters with Hmong in the US since 2007. The Hmong Music Festival, held in Fresno, California in 2012 and 2013, is used as a case study of attempts by American Hmong to build on the increasingly prominent digital diaspora to form an offline community of shared musical and cultural practices associated with their ethnicity. The cancellation of the festival in 2014 resulted in an online backlash that has challenged the continued existence of this annual event. The research shows that despite the vibrancy of online Hmong musical networks and the potential for developing offline connections, the Hmong digital diaspora are reaching the state of an enhanced imagined community in the cyber world, which may not be able to mobilise into a sustainable offline movement due to irreconcilable local and translocal differences.